1987
DOI: 10.1002/hon.2900050203
|View full text |Cite
|
Sign up to set email alerts
|

Treatment‐related leukemia in Hodgkin's disease: A multi‐institution study on 75 cases

Abstract: Hematological and cytogenetic characteristics of 75 cases of therapy-related acute non lymphoid leukemia (t-ANLL) occurring in Hodgkin's disease (HD) are analysed in this multi-institution study. Combined radio and chemotherapy had been given in 88 per cent of patients, either as adjuvant (44 per cent) or as salvage modality (44 per cent). Radiotherapy alone and chemotherapy alone had been given in 3 per cent and 9 per cent respectively. Eighty per cent of patients were in remission of HD and 71 per cent off-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
1

Year Published

1988
1988
2010
2010

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(4 citation statements)
references
References 58 publications
0
3
1
Order By: Relevance
“…Only a trend in a higher CR rate (74 vs. 51%, P \ 0.08) was observed for secondary AML following BC [42]. In contrary to observations in secondary AML in Hodgkin lymphoma patients [69], previous exposure to alkylating agents did not modify treatment response [42].…”
Section: Prognosis Of Shm After Bc Treatmentcontrasting
confidence: 50%
“…Only a trend in a higher CR rate (74 vs. 51%, P \ 0.08) was observed for secondary AML following BC [42]. In contrary to observations in secondary AML in Hodgkin lymphoma patients [69], previous exposure to alkylating agents did not modify treatment response [42].…”
Section: Prognosis Of Shm After Bc Treatmentcontrasting
confidence: 50%
“…Therapy-related MDS arises following exposure to alkylating agents with or without radiotherapy for primary cancers [4,6,16,25] and is an important long-term complication of bone marrow transplantation [28]. Secondary therapy-related MDS is characterized by bone marrow dysfunction [22,25], anemia and thrombocytopenia [8,22,30], karyotypic abnormalities [33,35,37] (especially loss of some or all chromosomes 5 and/or 7), and rapid transformation to acute leukemia [22] refractory to antileukemic therapy [18,19,23,34]. The hematological and cytogenetic findings relevant to our series of secondary MDS are in agreement with those in previous reports [34,37].…”
Section: Discussionmentioning
confidence: 99%
“…7,8 However, some authors reported it difficult to classify therapy-related disease by FAB criteria, mainly because many cases show marked multilineage dysplasia but fewer than 5% blasts in the blood or bone marrow, findings that do not fit well into any of the FAB subgroups. [19][20][21] Such cases could be classified by the WHO criteria as refractory cytopenia with multilineage dysplasia (RCMD), yet in that classification scheme, therapy-related acute myeloid leukemia (t-AML) and t-MDS are simply grouped together as a single syndrome (t-AML/MDS) and included with AML. 9 The WHO system further recognizes 2 subtypes of t-AML and t-MDS depending on the previous chemotherapy received by the patient (alkylating agent-related vs topoisomerase-II inhibitor-related disease).…”
mentioning
confidence: 99%